Who is afraid of the pink elephant? Character evidence, wiretapping, and debiasing interventions - Christoph Engel; Jasmin Golder; Rima-Maria Rahal (Max Planck Institute for Research on Collective Goods, 2024)
Defendants should be judged on the merits of the case, not on prejudice, rumors, or evidence obtained through questionable methods. This is why criminal law of procedure regulates which information can be introduced in a trial. Two types of prohibited evidence are the criminal history of the defendant (the defendant shall not be considered more likely guilty since he had earlier been convicted for another crime), and information harvested from an unauthorized wiretap. In a series of online vignette experiments involving 1432 US participants, we show that character evidence never makes it significantly more likely that the defendant is judged guilty, whereas wiretap evidence has a strong effect. Various interventions aimed at debiasing the adjudicator have an effect, but this effect is insufficient to neutralize the bias.
hdl:21.11116/0000-0010-3C9F-9
Keywords: C91; D02; D84; D91; K14; K41; K42; 330; criminal procedure; character evidence; wiretap; bias; debiasing